2019
DOI: 10.1080/13691058.2019.1636290
|View full text |Cite
|
Sign up to set email alerts
|

Gender identity and sexual orientation development among young adult transgender men sexually active with cisgender men: ‘I had completely ignored my sexuality … that’s for a different time to figure out’

Abstract: View related articlesView Crossmark data Citing articles: 2 View citing articlesGender identity and sexual orientation development among young adult transgender men sexually active with cisgender men: 'I had completely ignored my sexuality … that's for a different time to figure out'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Specifically, at low levels of structural stigma, transgender respondents had later predicted ages of awareness and coming out, whereas cisgender participants had a later age of coming out and longer closet duration. Above, we suggested that later age of awareness among transgender (vs. cisgender) participants could result, in part, from the fact that many transgender people explore and relabel their sexual identities over the course of gender identity development (Hereth et al, 2020;Katz-Wise et al, 2016;Katz-Wise & Hyde, 2017). However, this research has primarily occurred in low structural stigma contexts in the US, and it is plausible that sexual identity exploration and relabeling is less common for transgender people in higher-stigma contexts.…”
Section: Structural Stigma and Differences In Developmental Milestone...mentioning
confidence: 89%
See 3 more Smart Citations
“…Specifically, at low levels of structural stigma, transgender respondents had later predicted ages of awareness and coming out, whereas cisgender participants had a later age of coming out and longer closet duration. Above, we suggested that later age of awareness among transgender (vs. cisgender) participants could result, in part, from the fact that many transgender people explore and relabel their sexual identities over the course of gender identity development (Hereth et al, 2020;Katz-Wise et al, 2016;Katz-Wise & Hyde, 2017). However, this research has primarily occurred in low structural stigma contexts in the US, and it is plausible that sexual identity exploration and relabeling is less common for transgender people in higher-stigma contexts.…”
Section: Structural Stigma and Differences In Developmental Milestone...mentioning
confidence: 89%
“…Relative to cisgender respondents, transgender respondents reported becoming aware of their LGB identity at later ages. These differences may stem from the close connection between sexual identity development and gender identity development: because sexual identity is often (though not always) predicated on one's gender, sexual identity and gender identity development are deeply intertwined for many people (Hereth et al, 2020). For transgender people, gender identity development is often complicated by structural anti-transgender stigma Price et al, 2021), which encourages people to repress gender identities that do not match sociocultural expectations for the sex they were assigned at birth, even at the level of their own awareness (Hereth et al, 2020).…”
Section: Subgroup Differences In Developmental Milestone Timing and P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to McLean et al, Hereth and colleagues describe a 'renegotiating' of gender positions (Hereth, Pardee, and Reisner 2020). The authors explore the ways in which young transgender men and non-binary men in the USA navigate the complexities of gender and sexuality, creating and 'doing' new forms of both as they go (Hereth, Pardee, and Reisner 2020). The participants in their qualitative study vary greatly in their gender expression and sexual preferences.…”
Section: Gender Justice and Their Applicationmentioning
confidence: 97%